Optoelectronic and photoelectric properties and applications of graphene-based nanostructures. (June 2020) - Wang, J.; Song, J.; Mu, X.; Sun, M.
Abstract: Due to its unique electrical and optical properties, graphene has considerable potential for optoelectronics applications. Graphene's ultra-high carrier mobility, ultra-strong ballistic transport effect, ultrafast optical response time, and ultra-wide spectral response range give it excellent micro- and nanoscale photoelectric properties. Graphene's optoelectronic and photoelectric properties are modified by varying the size, boundary configurations (zigzag or armchair), doping with other elements, and building heterostructures (in-plane or vertically stacked) to regulate the photoelectric properties of graphene-based nanomaterials. This review focuses on the novel photoelectric properties and potential applications of graphene-based nanomaterials. Graphical abstract: Image 1 Highlights: Graphene's ultra-high carrier mobility, ultra-strong ballistic transport effect, ultra-fast optical response time. Graphene's ultra-wide spectral response range give it excellent micro- and nanoscale photoelectric properties. Graphene's optoelectronic and photoelectric properties are modified by varying the size, boundary configurations (zigzag or armchair), doping with other elements. Building heterostructures (in-plane or vertically stacked) to regulate the photoelectric properties of graphene-based nanomaterials.